Open access policies: between rights and obligations - Wahid, Ratnaria; Mat, Bakri (IGI Global, 2016)
Scholarly publishing is central to the efficiency of research, dissemination of research findings and diffusion of scientific and technical knowledge.Studies however reported that gaining access to published research findings is still a problem due to the increasing costs of journal subscription, a system protected by copyright law. This chapter briefly explains open access and explores its strengths and weaknesses.It further explains why the UK accepted the Finch Report recommendations to encourage innovations by enabling more people to read and use research publications.This chapter emphasizes that the benefit of open access policy as an incentive to enhance innovation must be encountered with caution as it will bring varying implications for different countries and disciplines. It also argues that although those involved in scholarly publishing have the right to be fairly compensated, they also have the moral obligation to ensure its dissemination for the benefit of public interest.